The Dynamics Of Aging Process Adaptation From the Late Adulthood To the Elderly in Panti Werdha X - Putri, Jelite Prenggo; Natalia, Johanna (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Elderly refers to individuals aged 60 years and over. The aging process in the elderly occurs with a gradual decline in the ability and function of organs. This study aims to determine the dynamics of adaptation to the aging process from late adulthood to old age in the elderly at the Panti Werdha X nursing home. This study only used one participant with purposive sampling method criteria. This research is a case study that is assessed using the methods of observation, interviews, and psychological tests. The results showed that there was a decrease in cognitive function and stress that caused the delay in the aging adaptation process from late adulthood to the elderly. Suggestions are given to improve the welfare of the elderly in terms of physical and psychological. So that it can help the elderly reduce the stress experienced in the elderly phase because they do not have activities or busyness and can achieve happiness in the elderly. In addition, it can help the elderly reduce the stress experienced in the elderly phase because they do not have activities or busyness and can achieve happiness in the elderly. Lansia mengacu pada individu berusia 60 tahun ke atas. Proses penuaan pada orang tua terjadi dengan penurunan bertahap dalam kemampuan dan fungsi organ. Penelitian ini bertujuan untuk mengetahui dinamika adaptasi terhadap proses penuaan dari akhir masa dewasa hingga usia tua pada lansia di panti werdha X panti jompo. Penelitian ini hanya menggunakan satu peserta dengan kriteria metode purposive sampling. Penelitian ini merupakan studi kasus yang dinilai dengan menggunakan metode observasi, wawancara, dan tes psikologi. Hasil penelitian menunjukkan bahwa terjadi penurunan fungsi kognitif dan stres yang menyebabkan keterlambatan proses adaptasi penuaan dari akhir masa dewasa hingga lansia. Saran diberikan untuk meningkatkan kesejahteraan lansia dalam hal fisik dan psikologis. Sehingga dapat membantu lansia mengurangi stres yang dialami pada fase lansia karena tidak memiliki aktivitas atau kesibukan serta dapat mencapai kebahagiaan pada lansia. Selain itu, dapat membantu lansia mengurangi stres yang dialami pada fase lansia karena tidak memiliki aktivitas atau kesibukan serta dapat mencapai kebahagiaan pada lansia.